Topographical Distribution of the Phanerogamic Parasites in Sukna Forest, Darjeeling Distric, West Bengal - Ganguly, Pabitrananda; Kumar, Nirmal Chandra (Indian Forester, 1976)
A survey of the Phanerogamic parasites was made on 607.27 hectares of commercial forest in Sukana, West Bengal primarily to determine the effect of topographical elevations in the distribution of certain parasites. The data show. that the frequency of the parasites is highest on ridges, less on the slopes and least on the plains. The causes for such varied distribution in relation to topography are discussed.